Difference Influence of Price, Facilities, Location, Promotion and Income on Decision to Purchase Subsidized House in Green Leyangan 2 and Jepara Indah Regency Residences - Adityawarman, Abram; Wahyuningdyah, Retno Yustini (Journal of Management and Business Environment (JMBE), 2025)
Home or residence is one of the main elements for human to be able to survive. The purpose of this study was to identify the effect of price, facilities, locations, promotions, and income on the decision to purchase subsidized house in Green Leyangan 2 and Jepara Indah Regency residences and the difference of the influence between the two housings. This study used primary and secondary data with quantitative approach. The sample was withdrawn from the total subsidized homeowners in both housings amounted 164 using the rule of thumb of minimum 5 respondents for each variable. The total of 25 respondents were thus obtained from respectively those in Green Leyangan 2 and those in Jepara Indah Regency or totally 50 respondents. The questionnaire was distributed once the permission from the developer had been obtained. Price, facilities, locations, promotions, and income were proved to affect the decision to purchase subsidized house in both residences. There is a significant difference in the factors affecting the decision to purchase subsidized houses in Green Leyangan 2 and Jepara Indah Residences.